Metaevaluación del Programa Federal Fomento Ganadero: El caso del estado de Yucatán - Carlos Leyva Morales; Hansell Sabido Ocampo; Felipe Alonzo Solís (Atlantic Review of Economics (ARoEc), 2018)
– Discusses evaluations to assess its relevance and usefulness to the Fomento Ganadero program in Yucatán from 2001 to 2013. Used a longitudinal non-experimental design in the form of trend where recollection (literature review and key informant interviews) and analysis of information (principles on meta-evaluation of Diaz and Pacheco) was sustained in a mixed approach, qualitative and quantitative. Found that the assessments made to Fomento Ganadero in Yucatan in the period of interest, were generally of low quality and very shallow in terms of internal consistency of its coherence, rules of operation, quality, effectiveness and efficiency, impact, focus and sati sfaction of their beneficiaries, i.e. that its coherence not expressed itself in operating rules that define with precision indices of efficiency and effectiveness that sought to achieve the program, in a focus around the priority activities and target population that would benefit in the State and, in the precision of the parameters of impact and sa tisfaction which sought to achieve.
Keywords: H53; I38; M19; O21; Q18; 330; Public administration; Agricultural policy; Evaluation policy; Livestock development; Metaevaluation